2015
DOI: 10.4103/2279-042x.150053
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of surfactant via a thin intratracheal catheter in preterm infants with respiratory distress syndrome: Feasibility and outcome

Abstract: Objective:Currently, the method of early nasal continuous positive airway pressure (nCPAP) and selective administration of surfactant via an endotracheal tube is widely used in the treatment of respiratory distress syndrome (RDS) in premature infants. To prevent complications related to endotracheal intubation and even a brief period of mechanical ventilation, in this study, we compared the effectiveness of surfactant administration via a thin intratracheal catheter versus the current method using an endotrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 15 publications
8
105
1
Order By: Relevance
“…It should be emphasised that these improvements occurred despite surfactant delivery by the Hobart method occurring relatively late, at a median of 10 h, and only being applied to a minority of infants admitted at 29-32 weeks gestation. In these aspects, our study is at odds with several published studies of minimally invasive surfactant therapy in infants of similar gestation, in which around two-thirds of infants achieved the trial entry thresholds (FiO 2 0.30 or 0.35) at a very early age (<2 h) [12,13]. …”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…It should be emphasised that these improvements occurred despite surfactant delivery by the Hobart method occurring relatively late, at a median of 10 h, and only being applied to a minority of infants admitted at 29-32 weeks gestation. In these aspects, our study is at odds with several published studies of minimally invasive surfactant therapy in infants of similar gestation, in which around two-thirds of infants achieved the trial entry thresholds (FiO 2 0.30 or 0.35) at a very early age (<2 h) [12,13]. …”
Section: Discussioncontrasting
confidence: 53%
“…Findings of one observational study were consistent with this, with a low proportion of infants beyond 28 weeks gestation receiving surfactant treatment via thin catheter [8]. By contrast, other studies including infants at gestations above 28 weeks have reported that the majority of infants on CPAP qualified for the intervention [12,13], contrary to our experience at this gestation [6]. Full evaluation of the selective use of minimally invasive surfactant therapy should include information on what proportion of infants within the gestational age cohort qualified for the therapy, and of those, how many actually received it.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations